Of networks, hierarchies and conspiracies, or how a historic neoconservative bestseller is made - Viñao Frago, Antonio (Historia y Memoria de la Educación, 2020)
This critical essay is an extensive commentary-analysis of the work of historian Niall Ferguson entitled The Square and the Tower. Networks and Power from the Freemasons to Facebook translated and published in Spanish in 2018. The book is located, according to its author, on an intermediate path between dominant historiography, which has tended to underestimate the importance of networks, and conspiracy theorists, who usually exaggerate it. Its central purpose is to highlight the relevance that social networks have had and have in historical events and processes. The analysis carried out here is intended to unravel how this work is a good example, from the United States neoconservative field, of making a historic bestseller at the service of that ideology.